2015
DOI: 10.1016/j.landurbplan.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recycled aggregate growth substrate on green roof vegetation development: A six year experiment

Abstract: 15Green roofs can potentially be used to tackle a variety of environmental problems, and 16 can be used as development mitigation for the loss of ground-based habitats. Brown 17(biodiversity) roofs are a type of green roof designed to imitate brownfield habitat, but 18 the best way of engineering these habitats requires more research. We tested the effects with larger plant coverage and diversity before the occurrence of a sequence of drought 31 disturbances, but was more strongly negatively affected by the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 71 publications
1
18
0
3
Order By: Relevance
“…The seasonal variation partly may have been an artifact of our sampling protocol, which involved repeated destructive sampling of colonists. Repeated disturbances (hand-pulling of colonists) may have favored disturbance-adapted species (Grime, 1979;Myers et al, 2015); however, colonist management is common on green roofs, especially during early establishment, and green roofs are subject to repeated drought disturbances that can drive changes in plant composition (Bates et al, 2013(Bates et al, , 2015Brown and Lundholm, 2015). Accordingly, different patterns of disturbance, or the absence of disturbance, could result in different patterns in colonist composition than those observed in the current study.…”
Section: Temporal Variationmentioning
confidence: 73%
“…The seasonal variation partly may have been an artifact of our sampling protocol, which involved repeated destructive sampling of colonists. Repeated disturbances (hand-pulling of colonists) may have favored disturbance-adapted species (Grime, 1979;Myers et al, 2015); however, colonist management is common on green roofs, especially during early establishment, and green roofs are subject to repeated drought disturbances that can drive changes in plant composition (Bates et al, 2013(Bates et al, , 2015Brown and Lundholm, 2015). Accordingly, different patterns of disturbance, or the absence of disturbance, could result in different patterns in colonist composition than those observed in the current study.…”
Section: Temporal Variationmentioning
confidence: 73%
“…With regard to temporal trends in plant abundance, these essentially resemble successional patterns known from ground-level habitats, with annual therophytes often dominating initial stages but declining afterwards, perennial species increasing [90][91][92], and shrubs or meadows developing in the long-term, depending on environmental constraints such as moisture [92]. Also, with increasing roof age, plant species spontaneously colonize roofs [42,45] and overall plant abundance tends to increase ( [43,89,93,94] but see [41,69]).…”
Section: Trends In Green Roof Species Abundancementioning
confidence: 82%
“…The challenge to maintain vegetation in thin, nutrient-poor greenroof media has driven research to promote vegetation persistence. Bates et al (2015) found plant recovery from drought was facilitated by media characteristics, with media high in crushed brick performing the best from a group of recycled aggregate materials tested. Additives for increasing the water holding capacity of media such as polyacrylamide gel have been shown to significantly increase plant recovery following a drought period (Young et al, 2015), while others have shown biologically based additives such as seaweed hold promise to improve both water and nutrient holding capacity of greenroof media (Vijayaraghavan and Joshi, 2015).…”
Section: Field Laboratory and Modeling Hydrologicmentioning
confidence: 96%